Imaging of Hip Pain: From Radiography to Cross-Sectional Imaging Techniques. (13th January 2016) - Ruiz Santiago, Fernando; Santiago Chinchilla, Alicia; Ansari, Afshin; Guzmán Álvarez, Luis; Castellano García, Maria del Mar; Martínez Martínez, Alberto; Tercedor Sánchez, Juan
Abstract : Hip pain can have multiple causes, including intra-articular, juxta-articular, and referred pain, mainly from spine or sacroiliac joints. In this review, we discuss the causes of intra-articular hip pain from childhood to adulthood and the role of the appropriate imaging techniques according to clinical suspicion and age of the patient. Stress is put on the findings of radiographs, currently considered the first imaging technique, not only in older people with degenerative disease but also in young people without osteoarthritis. In this case plain radiography allows categorization of the hip as normal or dysplastic or with impingement signs, pincer, cam, or a combination of both.